Factors Influencing Lecturers' Perceptions of the Use of Role Play Method in Postpartum Midwifery Teaching Using English - Ummah, Kholifatul; Mustofa, Bilqis; Fathiyyah, Nurul; Ganisia, Ainun; Imeldawati, Rakhmalia (Journal of English for Academic and Specific Purposes (JEASP), 2025)
English is the primary language used in global communication. In the context of midwifery services, the application of English aims to equip students with communication skills that support international clinical practice. One instructional method considered effective in achieving this goal is role play, which enhances students’ clinical communication skills and critical thinking abilities. However, the success of its implementation largely depends on lecturers’ perceptions and readiness. This study aims to explore the factors influencing lecturers’ perceptions of using role play in postpartum midwifery care instruction delivered in English. Grounded in constructivist theory and the communicative language teaching approach, this research employs a qualitative design through in-depth interviews with midwifery lecturers at Dr. Soetomo University, Surabaya. Additional data were collected via questionnaires covering demographic backgrounds, teaching experience, English proficiency, and attitudes toward instructional innovation.  The findings reveal that lecturers’ perceptions are influenced by English language proficiency, previous experience using role play, positive attitudes toward active learning, and institutional support. This study contributes to a deeper understanding of the dynamics between English language integration and active learning methods in midwifery education. The novelty of this study lies in its qualitative approach, which uncovers pedagogical adaptation processes in bilingual instruction contexts and highlights implications for professional development and the design of supportive learning environments.